Objectivity, Subjectivity and Statistical Evidence - Evans, Michael (Université d'Ottawa | University of Ottawa, 2014)
Introduction: Statistics has applications in many fields. The point behind all of these applications is that there are questions for which there is no obvious way that we can obtain definitive answers. The reason for this lies in variation, which can arise for many reasons, and this leads to uncertainty. The health sciences provides an excellent example of this as the variation among patients, such as physical, genetic and lifestyle characteristics, lead to different responses to a treatment for a health problem. We are then left with the questions of whether or not a treatment works and, if so, how well.